Frontiers of research on prices, diet costs & diet affordability - Headey, Derek D. (2022)
Derek Headey POLICY SEMINAR Are healthy diets affordable? Using new data on retail prices and diet costs to guide agricultural and food policy Co-organized by IFPRI, Tufts University, the World Bank, and Food and Agriculture Organization (FAO) JUL 15, 2022 - 10:00 TO 11:30AM EDT